Quantitative Analysis of BDNF/TrkB Protein and mRNA in Cortical and Striatal Neurons Using α-Tubulin as a Normalization Factor - Ma, Bin (2012)
The neurotrophin brain-derived neurotrophic factor (BDNF) and its receptor tyrosine kinase TrkB serve important regulatory roles for multiple aspects of the biology of neurons including cell death, survival, growth, differentiation, and plasticity. Regulation of the local availability of BDNF/TrkB at distinct subcellular domains such as soma, dendrites, axons, growth cones, nerve terminals, and spines appears to contribute to their specific functions. In view of the variance in size and shape of neurons and their compartments, previous quantitative studies of the BDNF/TrkB protein and mRNA lacked a robust normalization procedure. To overcome this problem, we have established methods that use immunofluorescence detection of α-tubulin as a normalization factor for the quantitative analysis of protein and mRNA in primary rat cortical and striatal neurons in culture. The efficacy of this approach is demonstrated by studying the dynamic distribution of proteins and mRNA at different growth stages or conditions. Treatment of cultured neurons with KCl resulted in increased levels of TrkB protein, reduced levels of BDNF mRNA (composite of multiple transcripts) and a slight reduction in BDNF protein levels in the dendrites from the cortex. The KCl treatment also lowered the percentage of BDNF and TrkB proteins in the soma indicative of protein transport. Finally, analysis of the rat cortical and striatal neurons demonstrated comparable or even higher levels of BDNF/TrkB protein and BDNF mRNA in the neurons from the striatum. Thus, in contrast to previous observations made in vivo, striatal neurons are capable of synthesizing BDNF mRNA when cultured in growth media in vitro. The analytical approach presented here provides a detailed understanding of BDNF/TrkB levels in response to a variety of neuronal activities. Our methods could be used broadly, including applications in cell and tissue cytometry, to yield accurate quantitative data of gene expression in cellular and subcellular contexts.